2018
DOI: 10.4209/aaqr.2017.04.0132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PM10 and PM2.5 Source Profiles of Fugitive Dust in Zhengzhou, China

Abstract: As a result of rapid urbanization, the road lengths and built-up areas in Zhengzhou are steadily expanding along with increasing fugitive dust emissions. Identifying the physical and chemical characteristics and the chemical profiles of fugitive dust is important in achieving effective atmospheric pollution management. In this study, soil dust, road dust (RD), building demolition dust, and cement (CE) were chosen as the research objects. A total of 94 dust samples were collected from 20 sites. PM 2.5 (particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Previous study by Zhang et al (2015) collected 24-h PM 2.5 samples every sixth day in Wuhan from August 2012 to July 2013, and the results about the EFs are traceable. It was also found that the EFs of Ba, Mn, and K were below 10, and the EF of Zn were above 10, which is consistant with the finding of Jiang et al (2017) in China.…”
Section: Enrichment Factormentioning
confidence: 53%
“…Previous study by Zhang et al (2015) collected 24-h PM 2.5 samples every sixth day in Wuhan from August 2012 to July 2013, and the results about the EFs are traceable. It was also found that the EFs of Ba, Mn, and K were below 10, and the EF of Zn were above 10, which is consistant with the finding of Jiang et al (2017) in China.…”
Section: Enrichment Factormentioning
confidence: 53%
“…As the core city of CPER, Zhengzhou is characterized by severe PM (particulate matter) pollution (Jiang et al, 2017(Jiang et al, , 2018d and is thus selected for this study. In recent years, comprehensive PM research has been conducted on the chemical characteristics of PM in Zhengzhou (Jiang et al, 2018b; regarding source apportionment (Jiang et al, 2018c, e;Liu et al, 2019), health risks (Jiang et al, 2019a, b), and emission-source profiles (Dong et al, 2019;Jiang et al, 2018a). However, no study has been performed on the sources and characteristics of HONO in Zhengzhou.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have carried out chemical characterisation of PM from demolition activities. Jiang et al (2018) analysed dusts in Zhengzhou, China, and compared the geological and chemical profile with road dust, soil dust, and cement dust. By mass, the mean particle size across all samples was similar with approximately 10% (wt.)…”
Section: Other Particulate Mattermentioning
confidence: 99%